1995
DOI: 10.1093/bja/74.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of preoperative anxiety: comparison of measures in patients awaiting surgery for breast cancer

Abstract: We have compared three measurements of anxiety to determine their equivalence in assessing anxiety before surgery. Forty-four patients awaiting breast cancer surgery completed the state scale of the state-trait anxiety inventory (STAI), the hospital anxiety and depression scale (HAD) and a 100-mm visual analogue scale (VAS). Analysis restricted to correlations between the scales gave the misleading impression that VAS scores were inconsistent with those of the HAD and STAI. However, when scores were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 7 publications
8
129
0
12
Order By: Relevance
“…First, there is no unequivocal cutoff value for the STAI to define high-anxiety. We used the earlier reported cutoff value of 45 and higher (Millar et al, 1995;Roth et al, 1998) which matches almost perfectly with the validated cutoff value of the HADS (Millar et al, 1995). Second, nonresponse at 5-year follow-up was present.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…First, there is no unequivocal cutoff value for the STAI to define high-anxiety. We used the earlier reported cutoff value of 45 and higher (Millar et al, 1995;Roth et al, 1998) which matches almost perfectly with the validated cutoff value of the HADS (Millar et al, 1995). Second, nonresponse at 5-year follow-up was present.…”
Section: Discussionmentioning
confidence: 84%
“…Scale scores range from 20 to 80 with higher scores indicating higher levels of anxiety (van der Ploeg et al, 1980). A STAI-State score of more than 44 defines an individual as highly anxious (Spielberger and Vagg, 1984;Millar et al, 1995). Applying this cutoff level, we defined men with pretreatment STAI-State scores equal to or below 44 as 'lowanxiety' and those with scores above 44 as 'high-anxiety'.…”
Section: Psychological Measuresmentioning
confidence: 99%
“…Previously, studies comparing the effectiveness and validity of these three scales found equivalent results in detecting preoperative anxiety. [42][43][44][45] In our study, VAS-A assessment scale was used as it would be a simple, rapidly applicable and a reliable method for urgent category-1 C/S performed parturients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the VAS system has been employed in other studies because it is easier to be used in routine clinical practice than the STAI. Furthermore, there are studies which have validated VAS compared with STAI (23)(24)(25). We therefore consider this to be a minor limitation.…”
Section: Main Endoscopic Diagnosis Principal (N %)mentioning
confidence: 99%